The Effect of Improving Preoperative Sleep Quality on Perioperative Pain by Zolpidem in Patients Undergoing Laparoscopic Colorectal Surgery: A Prospective, Randomized Study - Zhennan Xiao; Bo Long; Zeji Zhao (Pain Research and Management)
Background and Objectives. Opioids are essential in pain management after laparoscopic colorectal surgery while large dose may induce constipation and pneumonia. Ample evidence has demonstrated that postoperative analgesia can improve sleep quality. But the effects of improvement in sleep quality on postoperative pain have yet to be determined. The aim of this study was to investigate the effect of improving preoperative sleep quality by zolpidem on intraoperative analgesia and postoperative pain. Methods. A prospective, randomized study was conducted with 88 patients undergoing laparoscopic colorectal surgery. The experimental group (S group, n = 44) was given 10 mg of zolpidem tartrate one night before the surgical procedure, while no medication was given to the control group (C group, n = 44). The primary outcome was the intraoperative remifentanil consumption. Sufentanil consumption, average patient-controlled analgesia (PCA) effective press times, the visual analog scale (VAS) scores, and incidences of postoperative nausea and vomiting (PONV) were recorded at 6 h (T1), 12 h (T2), and 24 h (T3) postoperatively. Results. The intraoperative remifentanil consumption was significantly lower in the S group than that in the C group (p<0.01). Sufentanil consumption at 6 h and 12 h postoperatively was significantly lower in the S group than that in the C group (p<0.05); average PCA effective press times and VAS scores, at 6 h and 12 h postoperatively, were significantly lower in the S group than those in the C group (p<0.01); differences between groups 24 h postoperatively were not significant. No significant between-group difference was noted in the incidence of nausea and vomiting. Conclusion. Improving patients’ sleep quality the night before surgical procedure by zolpidem can decrease the usage of intraoperative analgesics and reduce postoperative pain.